High Speed Realistic Mobility Model for TN-Multi Lane Highway Environment - Varshini R.J, Vivitha; J, Naskath; B, Paramasivan (International Journal of Engineering and Technology, 2018)
Vehicular Ad-hoc Networks (VANETs) are self-forming networks built from moving vehicles. The most important quality of VANETs is the high mobility of nodes, which makes the mobility model as one of the most important parameters. The mobility pattern in the mobility models is used to simulate the movement of the vehicles, which plays an important role in developing an effective communication for the vehicular network. The challenge is to generate suitable microscopic mobility model from the correct and realistic dataset. In this paper, the work analyses the different type of data sources in terms of various mobility models. Finally, it proposes the effective mobility model for the high speed multi-lane highway scenario. Then the performance metrics are analyzed for this proposed model using mobility and network simulators.Â